2020
DOI: 10.1017/s0022215120001851
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between anosmia and hospitalisation in patients with coronavirus disease 2019: an otolaryngological perspective

Abstract: Objective A study was carried out to evaluate the relationship between anosmia and hospital admission in coronavirus disease 2019 patients. Methods The clinical data of 1534 patients with confirmed coronavirus disease 2019 virus were analysed. The study was conducted with medical records of 1197 patients (78 per cent). The basic characteristics of patients and symptoms related to otolaryngology practice were examined. The patients were divided into two groups according to their follow up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…The proportion of CoV(+) HCWs with olfactory and/or taste disorders varies greatly between studies: in an investigation by Lan et al 15.7% of the PCR-positive [ 41 ] and Lindahl et al 12.0% of the seropositive [ 17 ] show olfactory/taste disorders, whereas Villareal et al and Lombardi et al present considerably higher rates ranging from 70.0 to 76.9% [ 35 , 40 ] that accord with our data, where the respective figure is 77.1% for olfactory or taste disorders. Increasing awareness of these symptoms being related to Covid-19 and their suggested association with milder disease may account for the rates differing [ [42] , [43] , [44] ]. Younger age may also explain some of the variation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of CoV(+) HCWs with olfactory and/or taste disorders varies greatly between studies: in an investigation by Lan et al 15.7% of the PCR-positive [ 41 ] and Lindahl et al 12.0% of the seropositive [ 17 ] show olfactory/taste disorders, whereas Villareal et al and Lombardi et al present considerably higher rates ranging from 70.0 to 76.9% [ 35 , 40 ] that accord with our data, where the respective figure is 77.1% for olfactory or taste disorders. Increasing awareness of these symptoms being related to Covid-19 and their suggested association with milder disease may account for the rates differing [ [42] , [43] , [44] ]. Younger age may also explain some of the variation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…From being asymptomatic or having mild fever, cough, myalgia and chest pain to succumbing to respiratory failure or DIC, presentations of COVID 19 show a wide spectrum especially in India. In addition, ear, nose, and throat (ENT) symptoms, including loss of sense of smell and/or loss of sense of taste (STL) have been reported in several patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…10,13 Avcı et al reported incidence rates for anosmia and dysgeusia symptoms in patients with Covid-19 of 44.2 per cent and 43.9 per cent, respectively. 15 These authors conducted a study with one of the largest sample sizes, and reported that anosmia was associated with out-patient follow up rather than in-patient management. 15 In the present study, 34.7 per cent of the patients presented with loss of smell and 26 per cent presented with dysgeusia symptoms.…”
Section: Discussionmentioning
confidence: 99%